Evaluation of health and quality of life in apheresis patients – data from the WAA register. (October 2019) - Goto, J.; Newman, E.; Witt, V.; Deeren, D.; Blaha, M.; Lanska, M.; Gasova, Z.; Bhuiyan-Ludvikova, Z.; Hrdlickova, R.; Ramlow, W.; Prophet, H.; Liumbruno, G.; et al.
Abstract: Objective: : The World Apheresis Association (WAA) register contains data from more than 89 000 apheresis procedures in more than 12, 000 patients. The aim of this study was to evaluate functional health and quality of life (QoL) in patients during apheresis treatment. Material and methods: : Estimates of health condition (HC) were made in 40, 445 and of QoL in 22112 apheresis procedures. This study focused on a 10-step graded evaluation of HC (scale from: 'bedridden, unable to eat' to a level of 'athletic competition') and self-assessment of QoL (scale from: worst ever '0' to best ever '10'). Data were compared in relation to various apheresis procedures and if the patient underwent the first or subsequent apheresis procedure. Results: : Of the patients treated with plasma exchange (PEX) with centrifugation technique (n = 15787) 10% were 'bedridden, unable to come out of bed' while for patients treated with plasma filtration technique (n = 1018) the percentage was 27%. During the first procedure these figures were 16% and 30%, respectively. Self-estimates of QoL were graded 'zero' or '1' in 1.6% of patients during the first apheresis procedure; At the first contact patients undergoing PEX graded like this in 4.3%. Conclusion: : Many of the patients undergoing apheresis treatment have poor HC and QoL at the start of therapy. Of all therapeutic apheresis procedures patients undergoing PEX had the lowest score of QoL.